Study diabetes-related endothelial cell dysfunction in a hemodynamic microfluidic system - Liu, Xiaofeng (2016)
Diabetes mellitus is a common metabolic disease with worldwide increasingly high morbidity and mortality, which is a serious threat to human health. It can be classified into two types based on the response to insulin in human body. Type 1 diabetes, of which the patients’ pancreas cannot produce enough insulin, accounts for 10% of total amount of patients with diabetes. Type 2 diabetes, of which the cells of the patients cannot respond to insulin properly, makes up 90% of the total cases. The deficiency of blood glucose control in type 2 diabetes significantly increases the risk of long-term complications related to damage to blood vessels, which leads to the major mortality. Hyperglycemia has been proved to be associated with the development and progression of diabetic complications, but it cannot dramatically alter endothelial cell function independently. In our previous study, pulsatile shear stresses along the endothelium, which are the frictional forces caused by blood flow, were demonstrated to contribute significantly to affect vascular functions, which can induce ROS generation and mitochondria fission in endothelial cells. In this thesis, I have introduced a novel hemodynamic microfluidic system to investigate the hyperglycemia and pulsatile shear stress induced endothelial cell apoptosis. This system was developed to accurately simulate the pulsatile nature of the blood flow in a human artery. Apoptosis was determined by using endothelial cells expressing a fluorescent resonance energy transfer-based biosensor as well as double staining method and Hoechst staining under different levels of glucose and pulsatile shear stresses. Furthermore, plasma samples from healthy volunteers and patients with diabetes were compared to identify biological factors that are critical to endothelial disruption. Three types of microchannels were designed to simulate the blood vessels under healthy and partially blocked pathological conditions. Results showed that endothelial cell apoptosis rates increased with increasing glucose concentration and levels of shear stress. The rates of apoptosis further increased for 1.4 to 2.3-fold when hyperglycemic plasma was used in the experiments under all hemodynamic conditions. Under static conditions, little difference was detected in the rate of endothelial cell apoptosis between experiments using plasma from patients with diabetes and glucose medium, suggesting that the effects of hyperglycaemia and biological factors on the induction of endothelial cell apoptosis are all shear flow-dependent. A proteomics study was then conducted to identify biological factors, demonstrating that the levels of eight proteins, including haptoglobin and clusterin, were significantly down-regulated, while six proteins, including apolipoprotein C-III, were significantly up-regulated in the plasma of patients with diabetes compared to healthy volunteers. A further study was conducted to investigate the relationship between haptoglobin levels and demographics of patients with diabetes, which showed that the duration of diabetes may potentially associate with the risk of vascular complications. In conclusion, this dissertation introduces a hemodynamic microfluidic system to investigate the effect of hyperglycemia, pulsatile shear stress and plasma proteins on endothelial cell dysfunction and elucidates that pulsatile nature of blood flow is an indispensable factor of inducing endothelium damage. Last but not least, haptoglobin is a potential indicator for evaluating the risk of vascular complications in patients with diabetes.